The association between clinical manifestation, biochemical marker (ca125) and diagnostic laparoscopy or laparotomy findings with/without histopathological confirmation in the diagnosis of endometriosis - Suk Chin, Pang (2014)

(untitled)
Objective This study was performed to create a scoring system name Cli-Endomet, which suggestive of endometriosis, by evaluating the association between the medical history, clinical examination, ultrasound findings and biochemical marker ( CA 125 ). Methodology This was a cross sectional study, performed over 18 months duration from November 1st, 2011 until April 31st 2013. 176 patients with pelvic pain, which include dysmenorrhea, dyspareunia, ovulation pain, dyschezia or any chronic non-specific pelvic pain were recruited into the study. Detailed history and a thorough clinical examination were performed on each patient. A transvaginal ultrasound scan was performed and 2 mls of blood was taken from each patients either during menstruation or late luteal phase to determine the level of serum CA 125. All patients were then been subjected to either laparoscopy or laparotomy operation and/or tissue biopsy was taken for histopathology examination whenever was possible. In the presence of endometriosis, the staging of disease was determined using revised American Society of Reproductive Medicine (rASRM) scoring system. The clinical criterias which were strongly associated with diagnosis of endometriosis were extracted from statistical model, and were transformed for development of the clinical criteria scoring system, the Cli-Endomet. Results Among 176 patients recruited, 103 of them (58.5%) were confirmed to have endometriosis. The clinical manifestations and CA 125 level were analyzed via simple logistic regression then followed by multiple logistic regression, to determine the association between clinical presentation, CA 125 and endometriosis. The ROC (Receiver Operating Characteristic) curve of CA 125 was plotted and the cutoff points of CA 125 level in association with endometriosis were 50 to 200 U/mL with p value < 0.001. The clinical parameters which were statistically significant were dysmenorrhea ( especially severe type, p < 0.015 ), ultrasonography finding of ovarian mass (if present) with ground-glass appearance or thick with sediments content ( p < 0.001 ) and CA 125 level ( p < 0.001 ). From this analysis results, a scoring system Cli- Endomet was then developed. Conclusion CliEndomet scoring system, which takes into consideration of several significant clinical parameters, can be used as an alternative tool that suggestive of endometriosis. However, the accuracy of CliEndomet is not fully validated yet. Should it proven to be accurate, it may avoid patient from unnecessary diagnostic surgical procedure and further medical treatment may be instituted accordingly.